Amyloid protein aggregates: new clients for mitochondrial energy production in the brain?. (13th February 2020) - Sivanesan, Senthilkumar; Chang, Edwin; Howell, Mathew D.; Rajadas, Jayakumar
Abstract : Mitochondria are key organelles, which maintain energy metabolism and cellular homeostasis. Mitochondria support transcriptional regulation and proteostatic signaling mechanisms through crosstalk between the mitochondria itself, the nucleus, and the cytoplasm. Mitochondrial dysfunction leads to impaired proteostasis, and both are key pathological features of age‐related neurological disorders. For example, Alzheimer's and Parkinson's diseases feature mitochondrial‐targeted protein aggregates and impaired mitochondrial function, although the mechanistic causes are poorly understood. Vascular abnormalities and hypometabolism in such neurological diseases are reported several years before key clinical disease symptoms even become apparent. Recent investigations suggest that processing of such aggregates within mitochondria can offer protective functions, specifically by restoring energy (ATP) in starving cells. We hypothesize that the accumulation of protein aggregates in mitochondria can not only disrupt its functions, but also render a protective role to fulfill energy demands in hypometabolic conditions. Growing evidence favors mitochondrial defense to toxic amyloid aggregates/oligomers as a protective response. In this viewpoint article, we will present several publications (in addition to our own) that serve to connect the possible role of protein aggregates in mitochondrial energy production for degenerative conditions. Abstract : Amyloid aggregates targeting hypometabolic brain mitochondria in several neurodegenerative diseases are cleared by mitochondrial pathways/mechanisms to restore energy in the form of ATP. Increased urea cycle activation implicates amino acid catabolism and ammonia detoxification. The mitochondrial protective response involving mechanisms such as Wnt signaling, Prx5, HtRA2, and NMNAT defends the toxicity and damage caused by amyloid aggregates.